AUDIT MANAJEMEN UNTUK MENILAI EFEKTIVITAS FUNGSI PEMASARAN (STUDI KASUS PADA PT ASTRA INTERNATIONAL TBK-AUTO 2000 CABANG MALANG SUTOYO) - Apriliawati, Yesi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research aims to examine the effectiveness of marketing function at PT Astra International Tbk – AUTO 2000, Branch Malang Sutoyo. The scope of the study includes marketing environment, marketing strategy, marketing organization, marketing system, marketing productivity, and other marketing functions. This case study employs a qualitative approach. The data are collected through questionnaires, interviews, documentations, and observations. The analysis is carried out by comparing the criteria, causes, and effects, in which some advice or recommendations are given to improve the marketing functions. The study reveals that the marketing functions do not run effectively. Exhibitions and launchings of new products are administered less appropriately that they draw very few attentions from public. The company’s infrastructure neither supports marketing activities significantly. Therefore, it is suggested that the qualifications for the upcoming sales recruitment be improved.Keywords: Management audit, Marketing, Effectiveness